STEM-Based E-Modules to Improve Students' Critical Thinking in Economic Learning - Yani, Ni Luh Sinta; Rusdarti; Oktarina, Nina (Universitas Pendidikan Ganesha, 2024)
The scientific and technological advancements have rapidly progressed in the 21st century, especially in the field of education. Students need to be prepared for these advancements by possessing technical skills and critical thinking abilities necessary to support technology utilization. When students are unable to formulate critical questions, they are only capable of asking basic questions. This underscores the importance of critical thinking skills in teaching economics. This research aims to examine the feasibility of STEM-based e-modules and evaluate their effectiveness. This study falls under the classification of research and development (R&D) employing modifications from the Thiagarajan framework. The data analysis method applied in this study includes descriptive analysis concerning the module's feasibility. N-gain testing is utilized as a method to evaluate product effectiveness. The research findings indicate that: (1) the STEM-based e-modules created meet standards excellently in terms of language, content, and presentation; and (2) there is a noteworthy increase in the N-gain score, categorized as high in evaluating students' critical thinking abilities. These results support the notion that the created STEM-based e-modules can serve as an effective learning medium for Introduction to Economics within the economics education domain.